THE EFFECT OF WORK EVALUATION, COMPETENCE, AND REWARDS ON EMPLOYEE PERFORMANCE OF PT. SHARP SEMICONDUCTOR INDONESIA KARAWANG - Yunianto, Akhmad; Nadeak, Banuara; Solehudin, Solehudin; Nurhasanah, Nunung (Universitas Galuh, 2024)
PT. Sharp Semiconductor Indonesia (PT. SSI) is a foreign private company organization, which carries out production activities in Karawang, Indonesia. There are several problems as follows: 1) Employee performance has decreased, 2) The level of education is mostly at the vocational school/high school level, 3) Work evaluation is not fair and proportional 4) Decrease in operator multifunction, 5) Awards have not been given proportionally, 6) low operator wage value.This study aims to determine the description of employee work evaluation, competence, awards, and performance, to determine the relationship between work evaluation-competence, competence-awards, work evaluation-awards, to determine the effect of work evaluation, competence, and awards partially and simultaneously on employee performance.The method used is a quantitative approach with a descriptive and verification analysis design. The results of this study: work evaluation has fairly good criteria with an average value of 497.5 on a scale range of 389.9 - 509.9. Competence has good criteria with an average value of 541.0 on a scale range of 509.9 - 629.9. Awards have fairly good criteria, with an average value of 491.7 on a scale range of 389.9 - 509.9. Performance has good criteria with an average value of 522.0 on a scale range of 509.9 - 629.9.The correlation between Work Evaluation and Competence has a coefficient value of 0.783 (78.3%) in the interval of 0.600 - 0.799 which means strong. The correlation between Competence and Awards has a coefficient value of 0.781 (78.1%) in the interval of 0.600 - 0.799 which means strong. The correlation between Work Evaluation and Awards has a coefficient value of 0.658 (65.8%) in the interval of 0.600 - 0.799 which means strong. Job Evaluation has a partial effect of 0.0609 (6.09%), competency has a partial effect of 0.8428 (84.28%), partial reward of 0.0965 (9.65%). Job evaluation, competency, and reward have a simultaneous effect on employee performance of 0.951 or 95.1%.